2019
DOI: 10.1088/1361-6560/ab1442
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying T 2 relaxation time changes within lesions defined by apparent diffusion coefficient in grey and white matter in acute stroke patients

Abstract: Quantifying T 2 relaxation time changes within lesions defined by apparent diffusion coefficient in grey and white matter in acute stroke patients. Physics in Medicine and Biology, 64(9), [095016].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 31 publications
(80 reference statements)
2
16
0
Order By: Relevance
“…First, it was a pilot study with a modestly sized unselected cohort of people with stroke symptoms, consisting of strokes of varying size and severity, that occurred in different vascular territories and tissue types. Recent results suggest the time dependency of T 2 during the first 9 hours of stroke does not differ between grey and white matter, 18 but it is currently unclear whether this is true for different vascular territories. A previous study 27 found lesion size to be a mediating factor in the relationship of DWI image intensity ratios with time from onset.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, it was a pilot study with a modestly sized unselected cohort of people with stroke symptoms, consisting of strokes of varying size and severity, that occurred in different vascular territories and tissue types. Recent results suggest the time dependency of T 2 during the first 9 hours of stroke does not differ between grey and white matter, 18 but it is currently unclear whether this is true for different vascular territories. A previous study 27 found lesion size to be a mediating factor in the relationship of DWI image intensity ratios with time from onset.…”
Section: Discussionmentioning
confidence: 99%
“…25,47,48 The T 2 relaxation time also demonstrated higher overall ability at differentiating between scans performed before and after 3 hours from ischemia onset in rat models. 25 Patient studies have shown the T 2 relaxation time to have a strong linear relationship with time from symptom onset [16][17][18] Figure 6. PRG curves and AUPRG curves from the subcohort of patients with additional FLAIR scans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations